2012
DOI: 10.1590/s1413-35552012005000046
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre rigidez articular passiva e torque concêntrico dos rotadores laterais do quadril

Abstract: Background: Adequate passive stiffness of the hip joint can prevent the occurrence of excessive transverse plane lower limb movement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…According to Bittencourt et al, the medial hip rotation test is used to evaluate the ROM of internal rotation of the hip joint by measuring passive hip stiffness with a reference value between 30º and 40º, with an intraclass correlation coefficient (ICC) of 0.99 and a standard error of measurement (SEM) of 1.5° [17]. Leite et al reported that a value lower or higher than this mean directly interferes with the biomechanics of the entire lower limb, increasing the risk of injuries such as knee ligament ruptures and patellofemoral pain syndrome [18]. The mean values in the group were within the normal range, 36.14º in the right lower limb (standard deviation of ± 9.00) and 36.14º in the left lower limb (standard deviation of ± 7.70).…”
Section: Resultsmentioning
confidence: 99%
“…According to Bittencourt et al, the medial hip rotation test is used to evaluate the ROM of internal rotation of the hip joint by measuring passive hip stiffness with a reference value between 30º and 40º, with an intraclass correlation coefficient (ICC) of 0.99 and a standard error of measurement (SEM) of 1.5° [17]. Leite et al reported that a value lower or higher than this mean directly interferes with the biomechanics of the entire lower limb, increasing the risk of injuries such as knee ligament ruptures and patellofemoral pain syndrome [18]. The mean values in the group were within the normal range, 36.14º in the right lower limb (standard deviation of ± 9.00) and 36.14º in the left lower limb (standard deviation of ± 7.70).…”
Section: Resultsmentioning
confidence: 99%
“…For example, knee osteoarthritis has been shown to contribute to quadriceps weakness [31]. Weaker quadriceps would have presumably less passive stiffness [32] which, due to the patellar tendon's anatomical function as part of the quadriceps muscle-tendon unit [33,34], would most likely increase buckling within the patellar tendon. A potential effect of such extreme buckling is joint instability, which can lead to abnormal knee joint loading and increased degenerative wear [35].…”
Section: Discussionmentioning
confidence: 99%